BEAR ATTACKS IN JANGAMHATTI DHANGARWADA: INVESTIGATING CAUSES AND COMMUNITY RESILIENCE - Shinde, S. D.; Gavade, Vijay S. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The relationship between bear behavior and human activities, which often have negative impacts on both sides, is the main focus of this study on human-bear conflict in Jangmahatti Dhangarwada. The main causes of encounters are habitat loss, competition for resources, and environmental changes that force bears to move into populated areas in search of food or shelter. Such incidents are particularly common during the monsoon season, due to increasing agricultural activities and inadequate sanitation in rural areas. Due to their keen sense of smell, bears are frequently attracted to human settlements by the scent of food. These conflicts are exacerbated by factors such as competition, seasonal scarcity of natural food, and habitat loss. By focusing on regional perspectives and constraints, this study attempts to integrate ecological and social insights into human-bear interactions. The results are intended to provide strategies to enhance coexistence in comparable environments and address conservation issues. Such encounters are generally observed during the months of June and July. If a bear’s regular food source becomes scarce due to periodic changes, loss of territory, or hostility, it may wander into villages in search of food in garbage, produce, or animals. Similarly, bears are also attracted to animal dung. Focusing on the frequent attacks on the Dhangarwada settlement and its causes and impacts. Data was collected through interviews, field observations and review of past records to understand bear and human-wildlife interactions. The findings highlight the environmental and socio-economic factors that contribute to conflicts, as well as the vulnerability of local residents. Recommendations to reduce such encounters include community awareness programs and implementation of wildlife management policies.